High-quality pulse compression in a novel architecture based on a single-mode fiber cascading a nonlinear optical loop mirror - 徐永钊 宋建勋 张耿 刘敏霞 凌东雄 (Optoelectronics letters, 2016)
A novel all-fiber low-pedestal pulse compression scheme is proposed and investigated. The scheme is based on an anomalously dispersive single-mode fiber（SMF） cascading a nonlinear optical loop mirror（NOLM） with another anomalously dispersive SMF in the loop. Numerical results show that excellent pulse compression and pedestal reduction can be achieved by using the proposed scheme.